STRATEGI PUBLIC RELATIONS MELALUI MEDIA MONITORING DALAM MANAJEMEN REPUTASI PT ASURANSI TUGU PRATAMA INDONESIA TBK - Viko Rachmatullah Putra (2020)
At this time the media is developing very rapidly, various kinds of media are increasingly emerging such as online media or internet media, social media, conventional media and new media. The development of these media encourages people to more easily believe in things or information conveyed in the media. Like the news about various companies in the media. Society tends to always believe in what is conveyed by the media without thinking. This can affect the opinions, behavior and worldview of the company. Therefore, to find out the various views and opinions of the public towards the company, the company implemented a public relations strategy, namely Media Monitoring. The purpose of this research is to see how effective the monitoring media is in helping PT Asuransi Tugu Pratama Indonesia Tbk to manage its reputation, and how the public relations strategy is carried out by PT Asuransi Tugu Pratama Indonesia Tbk. This research was conducted through qualitative research methods with case studies, as well as conducting interviews in researching needed research data. The results of this study found that media monitoring conducted by the company was very helpful in evaluating various public relations strategies undertaken by PT Asuransi Tugu Pratama Indonesia Tbk so that it can be said that media monitoring carried out effectively in managing the reputation of PT Asuransi Tugu Pratama Indonesia Tbk.